10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
The Democratic Republic of Congo (DRC) is among the sub-Saharan African countries with a high neonatal mortality rate. Various interventions have been implemented to reduce this mortality rate, including the establishment of free maternity policy. This study evaluated the neonatal and maternal factors influencing infant mortality at 6 weeks of life. A prospective cohort study was conducted on infants recruited between March and July 2024 from maternity wards in Kinshasa, DRC. The cohort was followed for up to 6 weeks with home visits. The statistical analysis used Kaplan-Meier and adjusted Cox models. The multivariate Cox model was fitted with variables selected by LASSO and missing data were imputed using multiple imputation according to Rubin's rules. Among a cohort of 2,383 infants followed, 3.2% had a low-5 minutes Apgar score and 96.8% had a normal Apgar score. One of five babies with low 5-minutes Apgar scores died by the age of six weeks. Overall, the early postnatal mortality was 2.2% (95% CI: 1.67-2.85) with an overall mortality incidence of 0.53 deaths per 1,000 person-days. Multivariate Cox regression analysis with multiple imputation identified statistically significant increases in the associations of early postnatal mortality risk for low-5 minutes Apgar score (aHR: 9.96; 95% CI: 7.01-14.17), low birth weight (aHR: 3.57; 95% CI: 2.39-4.72) and prematurity (aHR: 1.97% CI: 1.26-3.12). Conversely, antenatal visits were a protective factor, with each additional antenatal visit associated with a 19% reduction in the risk of infant mortality (aHR: 0.81; 95% CI: 0.66-0.99). These results underscore the crucial importance of high-quality obstetric and neonatal care, as well as antenatal monitoring, for improving newborn survival. They call for strengthened antenatal care, improved screening and management of at-risk newborns in healthcare facilities, and the integration of these indicators into strategies for reducing neonatal mortality in resource-limited settings.